PERBANDINGAN SISTEM PENGAPIAN CONTACT POINT, TRANSISTOR CONTROLLED IGNITION (TCI -K) DAN PENGAPIAN FULL TRANSISTOR TERHADAP EMISI GAS BUANG PADA MOBIL L300 BENSIN 1500 CC - Ainun Ikbal, Alif; Budiyono, Budiyono; Prasetyo, Imam (Universitas Muhammadiyah Pekajangan Pekalongan, 2021)
Basically any engine that undergoes a combustion system to produce power allows for exhaust emissions. Exhaust gas emissions are the residue from the combustion of fuel (gasoline) and air in the combustion engine which is released through the engine exhaust system. Therefore, one of the efforts to reduce exhaust gas levels is to innovate to create a more perfect ignition system. This study aims to determine how the effect of the comparison of the ignition system Contact point, TCI and Full Transistor on the resulting exhaust emissions. The test was carried out using a gas analyzer on a Mitsubishi L300 gasoline with engine speed variations of 700 rpm, 1000 rpm, 2000 rpm and 3000 rpm to determine the concentration values of CO and HC. Based on the test results, it was found that the use of the TCI ignition system resulted in the lowest concentration reduction, namely at 3000 rpm engine speed with 1.43% CO levels and 115 ppm HC.Keywords: Contact point, TCI, Full transistor, Exhaust Emission